Ashwagandha: Optimizing the Extraction and Electrospun Nanofiber Production - Maciej Jaskólski; Magdalena Paczkowska-Walendowska; Andrzej Miklaszewski; Judyta Cielecka-Piontek (Pharmaceutics, 2025)
Background/Objectives: This study explores the development of electrospun nanofibers incorporating bioactive compounds from Withania somnifera (Ashwagandha) root extract, focusing on optimizing extraction conditions and nanofiber composition to maximize biological activity and application potential. Methods: Using the Design of Experiment (DoE) approach, optimal extraction parameters were identified as 80% methanol, 70 °C, and 60 min, yielding high levels of phenolic compounds and antioxidant activity. Methanol concentration emerged as the critical factor influencing phytochemical properties. Electrospinning technology was employed to produce nanofibers using polyvinylpyrrolidone (PVP) and hydroxypropyl-β-cyclodextrin (HPβCD) as carriers, ensuring encapsulation, stabilization, and an enhanced bioavailability of the active compounds. Results: Nanofibers demonstrated a high surface-to-volume ratio, rapid dissolution, and significant mucoadhesive properties, making them suitable for oral mucosal applications. The optimal nanofiber composition was determined to be 2.5 mL extract, 25% PVP, and an extract-to-HPβCD ratio of 1:0.6. Statistical modeling confirmed that the electrospinning process did not compromise the antioxidant or anti-inflammatory properties of the extract, with extract content being the primary determinant of biological activity. Conclusions: These findings highlight the potential of integrating advanced extraction techniques with nanotechnology to develop innovative delivery systems for traditional herbal remedies. The developed nanofibers offer promising applications in pharmaceuticals, cosmetics, and functional foods, paving the way for a scalable and efficient utilization of Ashwagandha bioactives.